Imperial powers and humanitarian interventions - Cheriau, Raphaël, 1976- author.
1 online resource (xiii, 254 pages)
Keywords: "In the second half of the nineteenth century, the Zanzibar Sultanate became the focal point of European imperial and humanitarian policies, most notably Britain, France, and Germany. In fact, the Sultanate was one of the few places in the world where humanitarianism and imperialism met in the most obvious fashion. This crucial encounter was perfectly embodied by the iconic meeting of Dr. Livingstone and Henry Morton Stanley in 1871. This book challenges the common presumption that those humanitarian concerns only served to conceal vile colonial interests. It brings the repression of the East African slave trade at sea and the expansion of empires into a new light in comparing French and British archives for the first time"--